Transitional Care Experiences Across Different Health Care Settings - Brooks, Laura (University of Waterloo, 2018)
Background: Older adults with multiple chronic conditions typically require care from numerous specialized health care providers across various different settings, making it necessary for patients to transition between these providers and settings (Institute of Medicine, 2001; Coleman, 2003). Transitions of care often result in discontinuities in care, leading to unmet patient needs, adverse events, and poor satisfaction with care, especially in patients with multiple chronic conditions, such as patients with hip fracture (Coleman & Boult, 2003; Naylor, 2000; Naylor, et al., 2009; Jaglal et al., 1996). This project aimed to understand how experiences of patients with hip fracture, family caregivers, and health care providers may differ across different points of transition. Methods: A secondary analysis of 103 qualitative, semi-structured interview transcripts was conducted to gain an understanding of how transitional care experiences may differ across varying settings of care. The analysis was completed using emergent coding techniques according to Braun & Clarke (2006) and Lofland & colleagues (2006). The results of this analysis were presented in a focus group interview, where participants who represented various roles across the health system were asked to comment on how the secondary analysis results fit their experiences and the current context of the health system. Results of the focus group interview were similarly analyzed using emergent coding techniques (Braun & Clarke, 2006; Lofland et al., 2006). Results: Seven key themes, each relating to various distinct transitional care settings, emerged from the secondary analysis: (1) Patients and family caregivers felt uninformed; (2) Multiple different providers contributed to patient and family caregiver confusion; (3) Transitions increased stress in patients and family caregivers; (4) Family caregivers were not considered important in the patient’s care; (5) Care was not tailored to patient needs; (6) System related issues impacted care experience; (7) Providers faced barriers in getting adequate information. The focus group interview results built upon these themes, adding an additional five related themes: (1) Enhancing knowledge and understanding in patients and family caregivers is important for safe and effective transitions; (2) Appropriate collaboration and communication between health care professionals improves transitions; (3) Consistency in health care providers can support system navigation and transitional care; (4) Development of system solutions should involve input from patients, caregivers, and front-line providers; (5) Transitional care may be improved through interventions aimed at enhancing communication and information sharing. The secondary analysis and focus group interview revealed that experiences of patients, caregivers, and health care providers vary by transition type. Specifically, transitions to other formal care settings are experienced differently from transitions to home. Discussion: In transitions to formal care settings, similarities were largely related to feeling confused, while in transitions to home, similarities existed in regards to patients, caregivers and health care providers feeling unprepared. Interestingly, the findings of the secondary analysis related to transitions to home seem to overlap with key factors of existing transitional care interventions, many of which have been developed for transitions to home. Future research should further explore the ways in which other transition settings may impact patient, caregiver, and health care provider experience, and quality of care, for a variety of complex health conditions.
Keywords: Transitional Care; Qualitative Research; Secondary Analysis; Hip Fracture; Older Adults